Pengaruh Penggunaan Model Pembelajaran Inkuiri berbasis Laboratorium Mini Terhadap Keterampilan Berpikir Tingkat Tinggi Siswa - Sella Nazwa; Nur Alim Natsir; Rahmiati Darwis (IAIN Ambon, 2022)
This study aims to determine the effect of the mini-laboratory-based inquiry learning model on students' higher-order thinking skills on acid-base and salt-grade VII material at MTs Al-Anshor Ambon. The data collection instruments used were tests and questionnaires. The population in this study was class VII MTs Al-Anshor Ambon in the academic year 2021/2022 which consisted of 2 classes with a total of 19 students. Data on students' higher-order thinking skills analyzed using descriptive and inferential statistics showed an average value of 80.00 for the experimental class and 73.00 for the control class with a standard deviation of 7.07 and the average result of student activity in the learning process was 70.60. and 65.88. The results of hypothesis testing using t-test obtained tcount = 1.751 and at a significant level = 0.05 with dk = 17 obtained ttable = 1.740, thus tcount > ttable, then H1 is accepted and H0 is rejected. This means that there is a positive influence of the mini-laboratory-based inquiry learning model on students' higher thinking skills.